PUBLIC POLICY AND THE DEVELOPMENT OF MADRASAH DINIYAH: A Case Study from Sampang - Ismail, Ismail (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: A public policy does not appear suddenly without a certain background, because public policy is formulated to respond, and solve problems. Purpose: This research departs from the assumption that the Sampang Regency Government formulate the Regional Regulation No. 7 of 2019 concerning Madrasah Diniyah Takmiliyah because it is caused by certain conditions. Method: To confirm these assumptions, the researchers collected data from data sources within the Regional Government, DPRD, FKDT, and madrash diniyah organizer in Sampang District using interviews, observation and documentation. The data obtained is then analyzed by means of data reduction, data presentation, and conclusion/verification. Rresult: This research resulted that (1) the substance and (2) background of this Perdakab Sampang. The substance of Sampang Regional Regulation can be classified into six key aspects: 1) Objectives and targets of Madrasah Diniyah Takmiliyah; 2) Administration; 3) Rights and obligations of students, educators, parents, and the local government; 4) Curriculum; 5) Supervision and monitoring; 6) Funding. And the background of this regulation included: (1) Implementation of government decentralization; (2) Response Results Identification of problems, needs, and community aspirations; (3) NPM implementation; and (4) the reality of madrasah diniyah.